Kekuatan Ketakteraturan Sisi Modular Pada Graf Rantai C(nCm) - Budayana, I Nyoman; Sariyasa, Sariyasa (Jurnal Matematika; Vol 14 No 1 (2024), 2024)
Modular edge irregular labeling of graph G is an vertex labeling f from V(G) to {1,2,3,…,k}  which is induced a bijection w from E(G) to Zn , where w(xy) = f(x) + f(y). Modular edge irregularity strength of graph G, mes(G), is the minimum number k such that f is a modular edge irregular labeling on G. In this paper, we discuss the modular edge irregularity strength of chain graph C(nCm), for m = 4,6,and 8.